Annual report on the fiscal impact of the Programs and Services related to the Higher Education Veterans Service Act - Illinois. (Higher Education Veterans Service Act, 2010)
Public Act 96-133, the Higher Education Veterans Service Act requires the Illinois Board of Higher Education (IBHE) to compile annually from Illinois' community colleges and public universities information on the fiscal impact of the programs and services related to the requirements of the Higher Education Veterans Service Act (the Act).
Title from cover.
Report year ends June 30
Public Act 96-133, the Higher Education Veterans Service Act requires the Illinois Board of Higher Education (IBHE) to compile annually from Illinois' community colleges and public universities information on the fiscal impact of the programs and services related to the requirements of the Higher Education Veterans Service Act (the Act).
Keywords: Veterans / Services for / Illinois / Finance.; Veterans / Education / Illinois / Finance.